Pendampingan Gelar Karya dan Pentas Seni sebagai Wujud Pengaplikasian Projek Penguatan Profil Pelajar Pancasila (P5) pada Kurikulum Merdeka (SD Negeri 4 Karanganyar) - Cici Nugraheni Wirjosantosa (Politeknik Piksi Ganesha Indonesia, 2023)
The implementation of the Pancasila P5 Student Profile Strengthening Project activities in the form of Work Degrees and Art Performances is one of the independent curriculum project activities. Activities carried out at SD Negeri 4 Karanganyar with the theme Love for Culture and Love for the Environment are a means of appreciation that can foster children's talents and interests and can be used as a venue for innovation. The P5 Project application activity is also the culmination of the learning that has been gained during the last 2 semesters.